Pengaruh Social Media Marketing, Brand Experience, dan Digital Engagement terhadap Keputusan Mahasiswa Baru Memilih Universitas Cokroaminoto Yogyakarta - Vezy Tamara; Heri Prasetyo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of social media marketing, brand experience, and digital engagement on new students’ decisions in choosing Universitas Cokroaminoto Yogyakarta. This research used a quantitative associative approach. The population in this study consisted of all new students of Universitas Cokroaminoto Yogyakarta in the 2025/2026 academic year, totaling 198 students. The sampling technique used was total sampling or census, so all members of the population were used as respondents. Data were collected through questionnaires using a five-point Likert scale and documentation. Data analysis was conducted using validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination test, partial test, and simultaneous test with the help of SPSS version 25. The results showed that social media marketing had a positive and significant effect on new students’ decisions in choosing Universitas Cokroaminoto Yogyakarta. Brand experience also had a positive and significant effect and became the most dominant variable. Digital engagement had a positive and significant effect on new students’ decisions. Simultaneously, social media marketing, brand experience, and digital engagement had a significant effect on new students’ decisions in choosing Universitas Cokroaminoto Yogyakarta. These findings indicate that digital communication, emotional experience toward the university brand, and student engagement with digital channels are important factors in higher education marketing.